Varian Ideologi Keberagamaan Di Muhammadiyah - Huda, Sholihul (Islam Kontemporer, 2016)
Muhammadiyah is "text" religious social realities vibrant and dynamic, so it continues to experience the dialectic movement and change in society. That is, the Muhammadiyah will continue in the construction by its members to be adjusted with the contemporary social reality, though not considered stagnant, old-fashioned "traditional". Moreover, by carrying the Islamic reform movement (Tajdid), it is increasingly affecting the natural thinking Muhammadiyah members to think and behave in the modern demand, and this requires continuous re-reading of the MuhammadiyahVarian Moderate religious ideology. This variant understand Muhammadiyah ideology openly (inclusive). That is, keberdaan Muhammadiyah in the community are not alone, but coincide with other religious social movements (NU, PERSIS, Al-Irsyad, Shia, FPI, HTI, etc.), so it must be mutual respect and tolerance. The group is open to new changes, but still consider the puritan tradition Muhammadiyah. The group is basing his understanding on the rules of Usul al-Fiqh "al-Mukhafadhatu ala al-ashlah qadhimi wal akhdzu jadidi ala al-ashlah" (Maintain a good long and mmengambil new good). This variant can accept the discourse of liberalism, secularism, pluralism, tolerance, but not to be followed by all, if there is good then it can be adopted with the tradition of Muhammadiyah.